Quantitative analysis of molecular interactions in κ-carrageenan-Isovanillin biocomposite for biodegradable packaging and pharmaceutical applications using NMR, TOF-SIMS, and XPS approach - Mohd Aiman, Hamdan; Khairatun Najwa, Mohd Amin; Fatmawati, Adam (Elsevier Ltd, 2024)
This study explores the molecular interactions and structural changes in κ-carrageenan crosslinked with isovanillin to create a biocomposite material suitable for hard capsule and bio-degradable packaging applications. Proton Nuclear Magnetic Resonance (1H NMR) spectroscopy revealed chemical changes in the conjugate molecule, indicating improved electronegativity due to intermolecular hydrogen bonding between κ-carrageenan and isovanillin. Time-of-flight Secondary Ion Mass Spectrometry (ToF-SIMS) analysis revealed enhanced ion intensity due to intermolecular interactions, particularly between sulphate and hydrogen ions. X-ray Photoelectron Spectroscopy (XPS) study demonstrated that κ-carrageenan and isovanillin form stronger hydrogen bonds, with a shift in binding energy indicating higher electronegativity. These findings shed light on the molecular mechanisms that underpin the formation of the biocomposite material, as well as its potential for use in hard capsule and biodegradable packaging materials, addressing the need for sustainable alternatives in the pharmaceutical and packaging industries while also contributing to environmental conservation.